Ethical competence in a profession: Healthcare professionals' views - Jessica Hemberg; Håkan Hemberg (Wiley, 2020)
Abstract Aim Ethical competence is a crucial component for enabling good quality care but there is insufficient qualitative research on healthcare professionals' views on ethical competence. The aim of this study was to investigate healthcare professionals' views on ethical competence in a student healthcare context. Design A qualitative design and a hermeneutical approach were used. Methods The material consists of texts from interviews with healthcare professionals (N = 10) in a student healthcare context. The method was inspired by content analysis. Results One main theme and four subthemes emerged. The main theme was as follows: safeguarding the vulnerability of the other. The subthemes were as follows: using sensitivity to establish a trustful relationship, acting in an objective and flexible manner, using a reflective process in decision‐making, and maintaining confidentiality and honesty. Future research should focus on investigating ethical competence from various perspectives in student health care, for example the student perspective or observational studies.